Effects of Adding Spirulina platensis to Laying Hen Rations on Performance, Egg Quality, and Some Blood Parameters - CURABAY, B.; SEVIM, B.; CUFADAR, Y.; AYASAN, T. (Journal of the Hellenic Veterinary Medical Society, 2021)
This study was conducted to determine the effect of adding different levels of Spirulina platensis (SP) to laying hen diets on performance, egg quality, egg yolk color and some blood parameters. Sixty 60-week-old Lohmann LSL Classic laying hens were used in the study. The experiment was conducted in 15 subgroups with 4 hens in each cage, with 5 replications in 3 treatment groups. Three different diets were offered to laying hens; one control (based to wheat) and two supplemented with different levels (1 and 2%) of SP. As it was observed, the addition of SP to laying hen diets had no significant effect on live-weight change (LWC), egg yield (EY), egg mass, egg weight (EW), feed intake (FI), and feed conversion ratio (FCR) (p>0.05). Concerning the egg quality characteristics that were examined, the effects of SP on shell strength (SS), shell ratio (SR), shell thickness (ST), shape index (SI), albumen index (AI) and serum parameters were not statistically significant (p>0.05); egg yolk color characteristics (Roche Color Scale and L*, a*, b*) were affected by dietary SP supplementation (p<0.01). Addition of different levels of SP (1% and 2%) to laying hen diets caused a significant increase in egg yellow color values compared to the control group. According to the results of the study, the addition of 1% and 2% SP to the laying hen rations had a significant positive effect on egg yolk color, but did not cause a significant change in other parameters.